Fortolkningen af forhistorien - Warburton, David A. (Religionsvidenskabeligt tidsskrift, 2002)
The study of prehistoric religion is shrouded in difficulties inherent to any disclipline dealing with the expression of concepts prior to the invention of writing. Archaeological investigations have revealed evidence of cult activities dating back to at least 8000 B.C., but the interpretation of these activities has been inhibited by difficulties in the development of archaeological theory as well as religion. Until recently, prehistoric archaeological theory avoided the issue of religion, concentrating on typology and function. Excavations and interpretations are largely influenced by prevailing theory, and these decisively influence the capacity of those interested in religion to interpret archaeological material. The same danger arises when archaeologists attempt to interpret archaeological material in conceptual terms familiar to students of comparative religion, as they are obliged to draw on existing theory to define the new approach to prehistoric religion. The material is simply exposed to a new approach.The situation was quite different for historical archaeology where gods and temples were present from the beginning. Symbols and writing were so common as hardly to attract attention. In fact, the disclipline itself partially owed its existence to the Bible and thus religion actually determined the agenda, leading som specialists to assume that the temples controlled the economy. With prehistoric archaeology, the apporach was virtually the opposite.These theoretical difficulties make the interpretation of the earliest traces of religion in the archaeological record very difficult. The archaeological community neglected the findings of the Anatolian site of Catal Hüyük when it was initially excavated in the 1950's and 1960's, as the community was agreed that religion could not be studied, and the importance of religion on the site could not be neglected. With the changing agenda in the 1990's, the archaeologist Ian Hodder decided to re-open the excavations at Catal Hüyük with a view to exploring their meaning in symbolic or religious terms. His approach may contribute to a finely nuanced version of the significance of social pressures as a fundamental factor in the development of religion. Scholars from other disciplines should, however, remain aware that the interpretations by archaeologists are always influenced by research agendas in other disciplines. They cannot, however, neglect the importance of studying the field simply because it is possible.